2020
DOI: 10.35530/it.071.03.1626
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to improve the self-cleaning effect of the textile materials

Abstract: The objective of this study is to investigate the methods to create durable self-cleaning textiles by coating fabrics with TiO2-(1%)Fe-N-graphene (2%). To improve the adherence of the nanoparticles, the polyester/cotton woven fabrics were pre-treated with polyacrylic acid (PA), carboxymethylcellulose (CMC) and polyethylene polyamine resin (EZF). The pre-treated materials were immersed in a doped TiO2 for 30 minutes at 40oC and dried at 125oC. The finished fabrics were stained with methylene blue dye an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…TiO 2 can be even used to improve the adhesion of nanoparticles on the fabric surface. 20,21 TiO 2 grains contain a band structure with a band gap between the empty high-energy conduction band (CB) and the electron-filled low-energy valence band (VB). The bandgap energy of anatase TiO 2 is 3.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 can be even used to improve the adhesion of nanoparticles on the fabric surface. 20,21 TiO 2 grains contain a band structure with a band gap between the empty high-energy conduction band (CB) and the electron-filled low-energy valence band (VB). The bandgap energy of anatase TiO 2 is 3.2 eV.…”
Section: Introductionmentioning
confidence: 99%
“…One of the manufacturing sectors that has drawn tremendous gains from nanotechnology is the textile sector. The application of nanotechnology in textiles has resulted in significant diversification and modification of the intrinsic properties of conventional textiles, for instance in improving the durability, comfort, hygiene related characteristics (Payne, 1997, Lee et al, 2003, Gorenšek and Recelj, 2007, Sun et al, 2009 and self cleaning properties, etc (Haji et al, 2016, Dumitrescu et al, 2020. Furthermore, application of nanotechnology has demonstrated that conventional textile products can be transformed into materials having an entirely new set of properties with an overall enhancement in the functionality too (Yuranova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%